Operational limits of a cascaded dual-output multilevel converter using model predictive control - Jayan, Vijesh (2022)
This article proposes a modified cascaded dual-output multilevel converter with a reduced number of power switches. The proposed converter can provide independent multilevel voltages across its dual-output ports, which makes it distinct when compared with the existing topologies. The mathematical model of the converter is developed for two converter cells with two output ports and is incorporated in a finite control set model predictive control algorithm for controlling the dual-output currents. Due to an inherent restriction, the converter output ports can operate independently, only during certain operating conditions. Therefore, converter operational limits in terms of voltage amplitude range are investigated for its output ports operating under various modes, such as different amplitude, different frequency, and different phase angle. The developed model is simulated for all these modes, and the operational limits of the proposed converter are obtained based on the distorted output currents. The effects of unequal dc source voltages on the operational limits are also analyzed. The determined operational limits ensure that the converter output ports operate independently without any current distortion and guarantee a safe operation. Finally, the operation of the proposed converter under different operating conditions is validated using simulation and experimental results.